EXPERIMENTAL FIELD CULTURE OF WHITE PRAWN, PENAEUS INDICUS, IN THE POLYETHYLENE FILM - LINED PONDS USING PELLETISED FEED - Lazarus, S; Muthu, M S; Nandakumaran, K; Ali, S A (Indian Journal of Fisheries, 2011)
The results of two experiments on the culture of Penaeus indicus conducted during the year 1982 aregiven. A high survival rate of 99.2% was obtained for the prawns which were stocked at a mean size of15.8mm. Maximum production rates obtained per hectare within a period of 83 days mono-culture understocking densities 4, 5, 7 and 10/m2 were respectively 355, 253, 431 and 398 kg. The size of prawnsat harvest ranged from 90.8 to 119.3 mm mean length and from 4.4 to 12.3 g mean weight. The instantaneousgrowth rate varied from 0.0211 to 0.0251 for length and from 0.0591 to 0.0720 for weight in thedifferent ponds. The pelletised feed used in these experiments gave a good feed conversion ratio of 2.62in one of the ponds.